2012
DOI: 10.1021/jo301458m
|View full text |Cite
|
Sign up to set email alerts
|

π-Extended Thiadiazoles Fused with Thienopyrrole or Indole Moieties: Synthesis, Structures, and Properties

Abstract: We report the syntheses, structures, photophysical properties, and redox characteristics of donor-acceptor-fused π-systems, namely π-extended thiadiazoles 1-5 fused with thienopyrrole or indole moieties. They were synthesized by the Stille coupling reactions followed by the PPh(3)-mediated reductive cyclizations as key steps. X-Ray crystallographic studies showed that isomeric 1b and 2b form significantly different packing from each other, and 1a and 4a afford supramolecular networks via multiple hydrogen bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 81 publications
1
40
0
Order By: Relevance
“…The absorption and fluorescence spectra of 4 – 8 were recorded in various solvents to investigate their photophysical properties in detail, and the relevant data for discussion are summarized in Table 1. We recently found that the longest absorption maxima (${\lambda {{{\rm abs}\hfill \atop {\rm max}\hfill}}}$ ) and the fluorescence maxima (${\lambda {{{\rm fl}\hfill \atop {\rm max}\hfill}}}$ ) are increasingly redshifted from 3 to 2 to 1 , and not only the nature of the aromatic rings fused with the pyrrole rings, but also their orientation affect the photophysical properties 10. Therefore the photophysical data for 4 – 8 are chiefly discussed from the viewpoint of the effects of 1) the extension of multifused π‐frameworks compared with 1 – 3 , that is, benzannulation, 2) the nature of the aromatic rings annulated to the pyrrole rings, that is, benzothiophene, naphthalene, and benzofuran, and 3) their orientation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorption and fluorescence spectra of 4 – 8 were recorded in various solvents to investigate their photophysical properties in detail, and the relevant data for discussion are summarized in Table 1. We recently found that the longest absorption maxima (${\lambda {{{\rm abs}\hfill \atop {\rm max}\hfill}}}$ ) and the fluorescence maxima (${\lambda {{{\rm fl}\hfill \atop {\rm max}\hfill}}}$ ) are increasingly redshifted from 3 to 2 to 1 , and not only the nature of the aromatic rings fused with the pyrrole rings, but also their orientation affect the photophysical properties 10. Therefore the photophysical data for 4 – 8 are chiefly discussed from the viewpoint of the effects of 1) the extension of multifused π‐frameworks compared with 1 – 3 , that is, benzannulation, 2) the nature of the aromatic rings annulated to the pyrrole rings, that is, benzothiophene, naphthalene, and benzofuran, and 3) their orientation.…”
Section: Resultsmentioning
confidence: 99%
“…The Φ f values in CH 2 Cl 2 for most compounds seem to be lower than those in other solvents, although the reason for this is unclear at present. We recently demonstrated that the moieties annulated to the pyrrole rings significantly affect the fluorescence efficiency 10. Compounds 1 and 2 display moderate‐to‐high Φ f values of 0.33–0.73 and 0.34–0.51, respectively, whereas 3 displays significantly low Φ f values of 0.04–0.07.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitrogen bridges not only planarize the molecular structure to induce stronger intermolecular π-π interaction but also play 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 5 an important role in determining the electronic and photophysical properties of the resulted polymers for OPV applications. The relatively low PCE of the N-bridged DTBT is mainly due to the high-lying HOMO and LUMO resulted from the strong electron donating ability of N atom 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, intermolecular frontier orbital overlap in molecular organizations is essential to enhance charge carrier mobility. The multifused aromatic and heteroaromatic compounds, for instance, are promising candidates on account of their flat and rigid frameworks, which provide the effective extension of π‐conjugation and allow for forming a dense molecular packing . Thus, they are expected to obtain spectacular properties such as strong fluorescence and high carrier mobility.…”
Section: Introductionmentioning
confidence: 99%